Enhanced recovery after posterior cervical fusion surgery: A retrospective case series - Kara L. Curley; Alexandra E. Richards; Nan Zhang; Mark K. Lyons; Matthew T. Neal (Interdisciplinary Neurosurgery, 2021)
Enhanced recovery after surgery (ERAS) is a multifaceted strategy, involving all phases of surgical care, intended to mitigate the stress response of surgery and optimize patient outcomes. A growing number of publications have demonstrated the benefits of ERAS protocols in specific populations of spine surgery patients. ERAS protocols have yet to be studied in patients undergoing posterior cervical decompression and fusion (PCDF) surgery. In this study, we compared the length of stay (LOS) and discharge disposition between two groups of patients that had PCDF surgery for degenerative pathologies. The pre-ERAS group consisted of 74 patients that had surgery between 2012 and 2017. The post-ERAS group included 25 patients that had surgery between 2017 and 2019. There were no significant differences between the two groups in terms of age, gender, and diagnosis (p greater than 0.05). The post-ERAS group had statistically non-significant, positive trends for LOS and discharge disposition. Implementation of an ERAS protocol for PCDF patients is feasible, however, future studies are needed to refine ERAS protocols and confirm the benefits.